“BEAUTY OF MEN” DANCE CHOREOGRAPHY - Arrofan Ryan Trisnawan; Nur Rokhim (ARTISTIC : International Journal of Creation and Innovation, 2021)
The evolution of high heels from women’s to men’s and finally to jockeys’ footwear in horse racing has attracted the authors. The wearers’ poses and movements can be elevated to a level of dance. Likewise, the drag queen in the Cabaret show faces difficulties in his personal and professional life. The choreographic form of “Beauty of Men” entails the creation of this dance. The dance work of  “Beauty of Men” is presented in ensembles. This dance work is composed and presented by developing dance movements. The dance work consists of four sections, beginning with introducing the self’s inner conflict. The first section designates the issues that confront families and communities. The second section describes the difficulties associated with social friendship. The third section illustrates the self’s difficulties and the quest for self-identity. Lastly, the fourth section expresses how the problems encountered were resolved. The process of creating the dance work of “Beauty of Men” reflects the dancer’s creative ability as a result of his experience.